2019
DOI: 10.1002/cctc.201900576
|View full text |Cite
|
Sign up to set email alerts
|

How Do Structurally Distinct Au/α‐Fe2O3 Interfaces Determine Surface OH/H2O reactivity, Intermediate Evolution, and Product Formation in Low‐temperature Water‐gas Shift Reaction?

Abstract: Three structurally distinct interfaces, i. e. Au/α‐Fe2O3‐THB‐Air, Au/α‐Fe2O3‐HS‐Air, and Au/α‐Fe2O3‐QC‐Air, with the major substrate facet being {113}, {001}, and {012} respectively, were controllably prepared. The low temperature water gas shift (WGS) reaction (100–260 °C) was applied to these unique systems to reveal how these structurally distinct interfaces can impact on the reaction behavior. With the detailed performance evaluation plus the characterizations of CO‐TPSR, XPS, and in situ‐FTIR in particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Our previous studies revealed that when the noble metals were deposited on the same kind of oxide with different facets, the resulting interfacial systems behaved very differently in a few catalytic reactions such as CO oxidation, water gas shi, hydrocarbon oxidation/ combustion, etc. [50][51][52][53][54][55] Here, not only the structural conguration but also the electron properties of the metal entity can be affected by the specic surface structure of the exposed SnO 2 substrate. In addition, the hydroxylation varies over the different facets of an oxide (specically SnO 2 in the current study), and the resulting OH species will be naturally distinct in reactivity.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…Our previous studies revealed that when the noble metals were deposited on the same kind of oxide with different facets, the resulting interfacial systems behaved very differently in a few catalytic reactions such as CO oxidation, water gas shi, hydrocarbon oxidation/ combustion, etc. [50][51][52][53][54][55] Here, not only the structural conguration but also the electron properties of the metal entity can be affected by the specic surface structure of the exposed SnO 2 substrate. In addition, the hydroxylation varies over the different facets of an oxide (specically SnO 2 in the current study), and the resulting OH species will be naturally distinct in reactivity.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…In this way, metal particles with controllable particle sizes can be precisely deposited onto the structurally clear oxide support to establish unique metal–oxide interfaces applied for certain catalytic processes and to achieve a structure–performance correlation in depth. This is the major tactic of the present study, and such tactics have been successfully applied for a variety of catalyst systems and reactions in our lab. …”
Section: Introductionmentioning
confidence: 99%